A New Vision on Schrödinger Equation Using Position Dependent Mass Concerning Modified Hylleraas-Hulthén Potential Expanded by Nikiforov-Uvarov Method - Abdulrahman N. Akour (The International Journal of Multiphysics, 2024)
Schrödinger equation is developed starting with position-dependent mass considering the quantum interacting potentials in quantum mechanics, that such called a modified Hylleraas-Hulthén potential where its developed using the Nikiforov-Uvarov approach. The wave functions are investigated and the energy eigenvalues and the related eigenfunctions are also determined